Marital satisfaction among the spouse of patient with severe mental illness in selected tertiary level hospitals. - Pandey,Anju (2020)
ABSTRACT: Marital satisfaction is an important aspect of general well-being which influences a person‟s quality of life uniquely, as no other relationship can. Global burden of mental illness is high and it usually affects marital satisfaction. The main objective of this study was to find out marital satisfaction among the spouse of patient with severe mental illness. A descriptive cross sectional study was conducted among 89 spouses of patient with severe mental illness in out-patient and in-patient Psychiatric Department of Tribhuvan University Teaching Hospital, Kathmandu and Mental Hospital, Lagankhel. Non- Probability purposive sampling technique was adopted. Data were collected by using socio-demographic and standardized Couple Satisfaction Index in Nepali version through structured interview method. Obtained data was entered in SPSS version 16.0 and analyzed by descriptive (frequency, percentage, mean and standard deviation) and inferential (Chi-square test) statistical methods. The findings of the study revealed that more than two fifth (41.6%) of the respondents were happy in their marital relationship Significant association was found between the level of marital satisfaction and age (p= 0.001), type of family (p= 0.011), type of residence (p= 0.007), duration of marriage (p=0.033), and perceived family support (p= 0.000) and phases of illness (p= 0.030). This study concludes that nearly two third of the spouses of patient with severe mental illness had marital satisfaction in their relationship. Satisfaction in marital relationship is essential for stability of marriage and decreases the relapse rate of mental illness so, it is recommended to concerned authority to conduct counseling program for the spouse of mentally ill patient which may help them to understand about mental illness and reduce their stress and uncertainty regarding their marital relationship.